The Role of Blockchain Technology in Improving Security and Transparency of Financial Transactions in Indonesia - Jen Surya; Iwan Efriandy; Reska Rahmatullah (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2025)
Blockchain technology has developed rapidly in recent years and is considered a promising solution for increasing security and transparency in financial transactions. Originally developed to support cryptocurrencies such as Bitcoin, blockchain is now being applied across various sectors, including banking and finance. This paper explores the role of blockchain technology in improving financial transaction systems, focusing on its ability to enhance security and transparency, thereby boosting user trust. It also examines the application of blockchain in Indonesia's financial sector, highlighting both the challenges and opportunities the country faces in adopting this technology. The methodology used in this study includes a qualitative analysis of existing literature on blockchain technology, case studies of its implementation in global financial systems, and an assessment of the regulatory landscape in Indonesia. The paper also discusses interviews with industry experts and stakeholders to gather insights into the practical challenges of blockchain adoption in the Indonesian financial sector. This research concludes with an analysis of blockchain's potential to revolutionize the global financial system, offering recommendations for its successful integration into Indonesia’s financial ecosystem.